PTH-309 Use of warmed humidified insufflation carbon dioxide to reduce surgical site infections in laparoscopic colorectal surgery: a cohort study. (22nd June 2015) - Noor, N; Reynecke, D; Hendricks, J; Motson, R; Arulampalam, T
Abstract : Introduction: Surgical Site infections (SSI) are a common complication associated with considerable morbidity. They have a negative impact on recovery time leading to extended hospital stay, reduced patient quality of life and constitute a financial burden to healthcare providers. The aim of this study was to evaluate if using HumiGard warmed, humidified CO2 insufflation system decreased the incidence of SSI. Method: A retrospective cohort study of two patient groups (n = 252 in a 1:1 ratio) undergoing laparoscopic colorectal resections in a specialist unit was undertaken; the first from Sept 2012 – July 2013 pre HumiGard and the second from July 2013–2014 with the HumiGard system. Data was retrieved retrospectively from case notes of all patients who underwent laparoscopic colorectal surgery with the HumiGard system and the same number of patients pre-intervention. The primary outcome was the between-groups difference in incidence of SSI, which was graded according to a standard classification system by an enhanced recovery team. Secondary outcomes were; differences in incidence of post-operative pneumonia, number of bed days and length of time in theatre recovery. In order to identify any change in outcomes, relative risk and odds ratios and their respective 95% confidence intervals were estimated as a measure of association for SSI, while RR was estimated for pneumonia. Bed-days and length of time in theatre recovery were analysed by ANOVA since these were continuous variables. Data was analysed in Genstat V.16. Results: Incidence of SSI was significantly reduced from 12% to 4.7% following introduction of Humigard (p = 0.047). A non-significant reduction in pneumonia was observed using HumiGard (4 vs 1, p = 0.21). Mean number of bed days decreased by 1.5 days (7.87 to 6.32) but did not reach significance (p = 0.16). Length of time spent in theatre recovery was similar (186 Vs. 190 mins p = 0.86). Mean body temperature post op was 36.5 ᵒC with Humigard, data was not recorded in the first cohort. Conclusion: The introduction of the HumiGard system in laparoscopic colorectal resectional surgery significantly reduced incidence of SSI. A trend was identified that it decreased pneumonia and length of stay, however these did not reach significance, therefore further data are required to more fully assess these outcome measures. With widespread use of laparoscopic surgical techniques now routine across surgical specialties in UK centres this study has identified an important intervention to reduce SSI. A randomised controlled trial to further assess the role of warming and humidifying insufflation gases in reducing the SSI and length of hospital stay is indicated. Disclosure of interest: None Declared.